Microbial ecosystem responses to alkalinity enhancement in the North Atlantic Subtropical Gyre - Subhas, Adam V.; Marx, Lukas; Reynolds, Sarah; Flohr, Anita; Mawji, Edward W.; Brown, Peter J.; Cael, B. B. (Frontiers in Climate, 2022)
In addition to reducing carbon dioxide (CO2) emissions, actively removing CO2 from the atmosphere is widely considered necessary to keep global warming well below 2°C. Ocean Alkalinity Enhancement (OAE) describes a suite of such CO2 removal processes that all involve enhancing the buffering capacity of seawater. In theory, OAE both stores carbon and offsets ocean acidification. In practice, the response of the marine biogeochemical system to OAE must be demonstrably negligible, or at least manageable, before it can be deployed at scale. We tested the OAE response of two natural seawater mixed layer microbial communities in the North Atlantic Subtropical Gyre, one at the Western gyre boundary, and one in the middle of the gyre. We conducted 4-day microcosm incubation experiments at sea, spiked with three increasing amounts of alkaline sodium salts and a 13C-bicarbonate tracer at constant pCO2. We then measured a suite of dissolved and particulate parameters to constrain the chemical and biological response to these additions. Microbial communities demonstrated occasionally measurable, but mostly negligible, responses to alkalinity enhancement. Neither site showed a significant increase in biologically produced CaCO3, even at extreme alkalinity loadings of +2,000 μmol kg−1. At the gyre boundary, alkalinity enhancement did not significantly impact net primary production rates. In contrast, net primary production in the central gyre decreased by ~30% in response to alkalinity enhancement. The central gyre incubations demonstrated a shift toward smaller particle size classes, suggesting that OAE may impact community composition and/or aggregation/disaggregation processes. In terms of chemical effects, we identify equilibration of seawater pCO2, inorganic CaCO3 precipitation, and immediate effects during mixing of alkaline solutions with seawater, as important considerations for developing experimental OAE methodologies, and for practical OAE deployment. These initial results underscore the importance of performing more studies of OAE in diverse marine environments, and the need to investigate the coupling between OAE, inorganic processes, and microbial community composition.